Evaluation of the efficacy, prognosis and safety of dexamethasone in the treatment of different types of non-puerperal mastitis: A retrospective study - Na Wang; Gang Hu; Lihua Xu; Lili Gong; Wanju Wang (PLoS ONE, 2025)
Objective To analyze the efficacy and safety of dexamethasone in the treatment of non-puerperal mastitis (NPM), providing a new idea for the treatment of NPM. Methods From August 1, 2017 to August 30, 2024, case data were collected from 552 patients with NPM. After grouping according to different treatment options, the SPSS statistical software was used for retrospective analysis of the collected data. Results The number of days of drug treatment before operation in group B was less than other groups (p < 0.001). The group B had the most significant relief of pain symptoms and shorter time to complete relief of pain than other groups (p < 0.001). There were statistically significant differences between the 5 groups in the time required for pain to disappear and the time required for the volume to be reduced by half after treatment (p < 0.05).The overall efficacy evaluation had the highest effective rate in Group B (100%) and the lowest in Group D (2.10%), and the difference was statistically significant (p < 0.001).No side effects such as abnormalities in liver and kidney functions, water-electrolyte disorders, or peptic ulcers were observed in the five groups during drug treatment. There was no statistically significant difference in the occurrence of side effects such as rash, diarrhoea and hyperglycaemia among patients in the five groups (p > 0.05).The side effects of nausea (vomiting) and skin pigmentation in group E were higher than other groups(p < 0.001). In terms of weight gain (full moon face), nervous excitability (insomnia) and menstrual disorders, group B was lower than other groups (except group D without hormone therapy)(p < 0.001). In terms of postoperative recurrence after ipsilateral breast surgery, the recurrence rates of patients in group B were lower than those of the other four groups, and group D had the highest recurrence rate (8.30%), with a statistically significant difference (p < 0.001). Satisfaction survey found that group B had the highest satisfaction rate other groups (p < 0.05). The number of days required for the volume to be reduced by half after treatment was the most influential factor in the satisfaction survey. At the same time, we found that the obvious effect and recovery rate of GLM group was higher than that of PCM group, and the difference was statistically significant (p < 0.05). Conclusion Dexamethasone combined with levofloxacin/Metronidazole in the treatment of NPM has many advantages: first of all, it can significantly relieve the pain symptoms caused by the disease and effectively reduce the size of the lesion. Meanwhile, for the patients who plan to undergo surgery, the number of days of preoperative drug treatment can be reduced, and the overall effective rate is the highest. Secondly, the short-term application of drugs to treat side effects less, high safety; in the meantime, the risk of recurrence of the ipsilateral breast was less and the satisfaction of the patients was higher. The overall significant efficiency and recovery rate of GLM patients were higher than those of PCM patients.